2022
DOI: 10.1021/acs.est.2c02395
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Aging Treatment Activates V2O5/TiO2 Catalysts for NOx Abatement

Abstract: Thermal stability is crucial for the practical application of deNO x catalysts. Vanadia-based catalysts are widely applied for the selective catalytic reduction of NO x with NH3 (NH3-SCR). Generally, hydrothermal aging at high temperatures induces the deactivation of deNO x catalysts. However, in this work, a remarkable increase in low- and medium-temperature NH3-SCR activity was observed for a V2O5/TiO2 catalyst after hydrothermal aging treatment, especially at 750 °C for 16 h. After the vanadia-based cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Figure a illustrates the H 2 -TPR profiles of the catalysts, and the H 2 consumption is listed in Table . It was found that a main peak was located at 381 °C on the VTi catalyst, which was ascribed to the reduction of surface V 5+ species. ,, When cadmium was incorporated into the catalyst, the V 5+ reduction peak shifted to a lower temperature (311 °C) with a significantly reduced intensity, and a reduction peak of Cd 2+ appeared (271 °C). , It meant that the reduction of V 5+ species was strongly restrained, resulting from the interaction between cadmium and vanadium. After arsenic doping, the overlapping of As 5+ (395 °C) , and V 5+ (407 °C) species reduction peaks was recorded over VTi–As with an increased H 2 consumption (0.16 mmol/g).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure a illustrates the H 2 -TPR profiles of the catalysts, and the H 2 consumption is listed in Table . It was found that a main peak was located at 381 °C on the VTi catalyst, which was ascribed to the reduction of surface V 5+ species. ,, When cadmium was incorporated into the catalyst, the V 5+ reduction peak shifted to a lower temperature (311 °C) with a significantly reduced intensity, and a reduction peak of Cd 2+ appeared (271 °C). , It meant that the reduction of V 5+ species was strongly restrained, resulting from the interaction between cadmium and vanadium. After arsenic doping, the overlapping of As 5+ (395 °C) , and V 5+ (407 °C) species reduction peaks was recorded over VTi–As with an increased H 2 consumption (0.16 mmol/g).…”
Section: Resultsmentioning
confidence: 98%
“…It was found that a main peak was located at 381 °C on the VTi catalyst, which was ascribed to the reduction of surface V 5+ species. 21,43,51 When cadmium was incorporated into the catalyst, the V 5+ reduction peak shifted to a lower temperature (311 °C) with a significantly reduced intensity, and a reduction peak of Cd 2+ appeared (271 °C). 15,18 It meant that the reduction of V 5+ species was strongly restrained, resulting from the interaction between cadmium and vanadium.…”
Section: Exploration Of Vox Species Changementioning
confidence: 99%
“…21-1272) and rutile (JCPDS No. 21-1276) phases of crystalline TiO 2 were identified without boric acid or titanium borate impurities. No Ru diffraction peak was identified due to the low loading and/or high dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 as a semiconductor metal oxide makes it easy to synthesize the TiO 2 -NTs (TNTs) structure with adjustable shape, in which tubular structures are considered the most suitable method for achieving more significant surface area increases without increasing the geometric area. 13 By modifying the reaction conditions, TNTs produced by anodic oxidation and electrochemical reduction may accurately regulate the structural characteristics (pore size, wall thickness, and length). A strong support structure is provided by the ordering and the closely packed nanotubes, which enables the loading of a particular photoactive material and lessens the loss of light reflection brought on by various radiation scatters.…”
Section: Introductionmentioning
confidence: 99%